Tumor necrosis factor-alpha in patients with alopecia areata - Emina Kasumagic-Halilovic; Asja Prohic; Semra Cavaljuga (Wolters Kluwer Medknow Publications, 2011)
Background : Alopecia areata (AA) is a common form of localized, nonscarring hair loss. It is characterized by the loss of hair in patches, total loss of scalp hair (alopecia totalis, AT), or total loss of body hair (alopecia universalis, AU). The cause of AA is unknown, although most evidence supports the hypothesis that AA is a T-cell-mediated autoimmune disease of the hair follicle and that cytokines play an important role. Aims : The aim of the study was to compare the serum levels of tumor necrosis factor-alpha (TNF-α) in patients with AA and the healthy subjects and also to investigate the difference between the localized form of the disease with the extensive forms like AT and AU. Materials and Methods : Sixty patients with AA and 20 healthy controls were enrolled in the study. Forty-six patients had localized AA (LAA), and 14 patients had AT, AU, or AT/AU. The serum levels of TNF-α were measured using enzyme-linked immunoassay techniques. Results: Serum levels of TNF-α were significantly higher in AA patients than in controls (10.31 ± 1.20 pg ml vs 9.59 ± 0.75 pg/ml, respectively). There was no significant difference in serum levels of TNF-α between patients with LAA and those with extensive forms of the disease. Conclusion : Our findings support the evidence that elevation of serum TNF-α is associated with AA. The exact role of serum TNF-α in AA should be additionally investigated in future studies.